Text Type-specific Aspects of Modality - a German-Italian Comparison - Baumann, Tania (ANNALI. SEZIONE GERMANICA. Rivista del Dipartimento di Studi Letterari, Linguistici e Comparati dell’Università degli studi di Napoli L’Orientale, 2021)
Text genres that are common in various linguistic and cultural communities are always balanced between translinguistic characteristics and language-specific features linked to historically established text genre conventions. This paper analyses from a contrastive textology perspective the interrelationship between the instructive function of travel guides and expressions of modality, such as modal verbs and imperative forms. A central question is whether specific linguistic expressions correlate with specific text functions and which convergences and divergences can be observed with that regard in German and Italian travel guides. The outcomes of contrastive text analysis can be useful both in the field of L2 didactics and in translation studies and translation training.